Testing the ability of ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) to map hydrothermal alteration zones : a case study of the Haib Porphyry Copper-Molybdenum Deposit, Namibia - Mhangara, Paidamwoyo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2005.